Effects of different dietary vitamin E and astaxanthin levels on growth, fatty acid composition and coloration of the juvenile swimming crab, Portunus trituberculatus. (14th February 2018) - Han, T.; Li, X.‐Y; Yang, Y.‐X.; Yang, M.; Wang, C.‐L.; Wang, J.‐T.
Abstract: Six isonitrogenous and isolipidic diets were formulated containing two astaxanthin (AX; 0 and 90 mg/kg) and three vitamin E (VE) levels (0, 25 and 50 mg/kg). There were three replicates (18 crabs per replicate) for each treatment. Juvenile swimming crab (initial weight 31.65 ± 0.06 g/crab) were fed different diets for 8 weeks. After the feeding trial, growth performance was not significantly affected by the different treatments. Crabs fed with AX‐supplemented diets showed more redness. Whole body 22:6n‐3, 22:4n‐6 and 20:5n‐3 levels increased with the dietary addition of AX ( P  =   .009, P  =   .002 and p  =   .042, respectively). The malondialdehyde (MDA) concentrations of fresh/frozen hepatopancreas and frozen muscle were significantly decreased by the dietary AX supplementation ( p <  .001, p  =   .010 and p  =   0.011, respectively). These findings provide evidence that dietary AX has an ability to improve the redness of the shell and reduce the MDA concentrations of tissues. Furthermore, there is no strong interactive relationship between dietary VE and AX on the coloration and fatty acid concentrations for the swimming crab.